Українсько-польські взаємини на сторінках шкільних підручників з історії України - Батуріна, С. (Історіографічні дослідження в Україні, 2019)
У статті пропонується аналіз сучасних шкільних підручників на
предмет представлення в них історії взаємин між українцями та
поляками впродовж тривалого періоду від середньовіччя до середини
ХХ ст. Серед основних завдань публікації є прослідкувати зміни, які
відбулися (чи не відбулися) у сприйнятті найближчого сусіда та відносин з ним, у порівнянні із попереднім поколінням українських підручників. Яким чином в них представлені поляки, польська держава та
спільне минуле від часів середньовіччя до сьогодення. До уваги взято
шкільні підручники для 5–11 кл., які отримали рекомендації до викладання в загальноосвітніх школах.
Відзначено, що поляки і Польща в текстах підручників з’являються
в певні історичні періоди, висвітлення кожного з яких відзначено особливостями, зумовленими економічними, політичними й суспільними
чинниками: доба середньовіччя – династичні контакти й мілітарні
конфлікти польських королів і руських князів; XIV – перша половина
XVIІ cт. – річпосполитський період від підпорядкування Польщею території Галицько-Волинського князівства і колишніх теренів Русі
до Хмельниччини; кінець XVIII–XIX ст. – від Коліївщини до відновлення
польської держави; період ХХ ст. Спільним для висвітлення усіх цих
періодів, попри специфіку та унікальність, є наявність конфлікту. Історія Польщі та україно-польських взаємин актуалізується в підручниках майже виключно через конфронтацію між обома народами в політичній чи військовій площині. The article presents an analysis of current school textbooks for the
purpose of presenting in them the history of relations between Ukrainians
and Poles during the long period from the Middle Ages to the middle of the
XX century. Among the main objectives of the publication is to track
changes that have (or have not) occurred in the perception and relationship
of the nearest neighbor, compared to the previous generation of Ukrainian
textbooks. How do they represent the Poles, the Polish state and the
common past from the Middle Ages to the present? The school textbooks for
grades 5–11 were taken into account, which received recommendations for
teaching in secondary schools.
It is noted that the Poles and Poland appear in the textbooks during
certain historical periods, each of which is highlighted in the textbooks by
specific economic, political and social factors: the Middle Ages – dynastic
contacts and militaristic conflicts between the Polish kings and Russians;
XIV – first half of XVI c. – the Commonwealth period from the subordination
by Poland the territory of the Galicia-Volyn principality and the
former territories of Russia to Khmelnytskyi war; the end of XVIII–
XIX c. – from the Koliivshchyna to the restoration of the Polish state;
period of the twentieth century. Common feature for all these periods,
despite the specifics and uniqueness, is the existence of conflict. The history
of Poland and the Ukrainian-Polish relationship is actualized in textbooks
almost exclusively because of a confrontation between the two nations in
the political or military aspects.
In most of the textbooks Poles, as representatives of the ethnic group are
represented to a very small extent. They are replaced by the image of
Poland as a state, and the relations of Ukrainians with the Poles are
considered only through the prism of state or political. The Poles, as
representatives of the ethnic group, appear in the texts, except in statistics,
illustrating the national composition of the Ukrainian territories geographically
and chronologically. Compared to the previous generation of
Ukrainian school textbooks, in modern editions old Soviet categories and
ethnocentric connotations are not so explicit. Authors attempt to find
compromises, identify the root causes of conflicts, avoid their unilateral
characterization, and make no alternative assessments.